Local clusters of anthropophytes and their migration in the ‘Murcki Forest’ nature reserve (The Silesian Upland) - Wika, Stanisław; Gorczyca, Monika (Biodiversity: Research and Conservation, 2006)
This paper presents the results of the studies on the occurrence and distribution of alien species in the “Murcki Forest” nature reserve, located in the city of Katowice. Most of the 26 recorded anthropophytes was found along forest roads and paths. Some alien species were noted on the edges of the nature reserve and in habitats associated with illegal rubbish dumps. Some, such as Aesculus hippocastanum, Impatiens parviflora, Padus serotina, Parthenocissus inserta, Pinus strobus, Quercus rubra, Ribes rubrum, and Robinia pseudoacacia, invaded into the interior of the forest. The most invasive species occurring quite strongly represented in typical forest habitats is Impatiens parviflora.